Synergistic effect of iron-oxide NPs conjugated with antibiotics against gram-positive and gram-negative bacteria - Nandi, Kishan; Rabbi, Abed Hasan; Mati, Mimisha Nishat (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.